1997
DOI: 10.3109/09513599709152565
|View full text |Cite
|
Sign up to set email alerts
|

Spacing-out of progestin - efficacy, tolerability and compliance of two regimens for hormonal replacement in the late postmenopause

Abstract: Estrogen replacement therapy with sequential progestin at greater than monthly intervals has been frequently used in practice to reduce progestational side-effects and bleeding episodes, but clinical trials are still lacking. Two new regimens were tested. The main objective was to evaluate efficacy, predominantly in urogenital complaints, tolerability, and patient acceptance. Transdermal estradiol (0.05 mg/day) and norethisterone acetate orally (2.5 mg/day) were administered for 12 days every 2 or 3 months (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
3
2
Order By: Relevance
“…With long-cycle (spacing out) therapy, an increased risk cannot be excluded (Bjarnason et al 1999), although we and others did not observe this (Rabe et al 1997, Erkkola et al 2002 (evidence level II-1). However, increased risk has also been demonstrated with addition of monthly sequential progestogen (SCEPT), in contrast to CCEPT (Weiderpass et al 1999, Hill et al 2000 (evidence level II-2).…”
Section: Eca During Ht -Primary Riskcontrasting
confidence: 53%
“…With long-cycle (spacing out) therapy, an increased risk cannot be excluded (Bjarnason et al 1999), although we and others did not observe this (Rabe et al 1997, Erkkola et al 2002 (evidence level II-1). However, increased risk has also been demonstrated with addition of monthly sequential progestogen (SCEPT), in contrast to CCEPT (Weiderpass et al 1999, Hill et al 2000 (evidence level II-2).…”
Section: Eca During Ht -Primary Riskcontrasting
confidence: 53%
“…It is well recognised that the primary risk for an ECa can be reduced through a combination with progestogen every cycle for a minimum of 10, or even better, 12 to 14 days [12]. With long-cycle (spacing out) therapy an increased risk cannot be excluded [13] although we and other authors did not observe this [14,15]. However, an increased risk has also been demonstrated with monthly sequential progestogen addition (SCEPT) in contrast to CCEPT (Table 1) [16,17].…”
Section: Endometrial Cancer During Ht − Primary Riskcontrasting
confidence: 47%
“…Preliminary data with quarterly norethindrone acetate, 2.5 mg for 12 days, showed that 61% experienced a withdrawal bleeding that lasted a mean of 4.8 AE 1.6 days in women using 50-mg estradiol patches. 141 Withdrawal bleeding averaged one half day less when the progestin was given every other month. Hirvonen et al 142 gave more than 200 women an average of 1 mg of estradiol transdermal gel daily opposed by 10 mg of oral medroxyprogesterone acetate (MPA) for 12 days every 28-or 84-day cycle.…”
Section: Dosing For Systemic Hormone Therapymentioning
confidence: 99%